A vertical gradient of nitrous oxide below the subsurface of the Canada Basin and its formation mechanisms. Issue 3 (30th March 2015) - Zhan, Liyang; Chen, Liqi; Zhang, Jiexia; Li, Yuhong
Abstract The ocean is regarded as a significant source of N2O, which is an ozone‐depleting greenhouse gas. However, the contribution of the Arctic Ocean to the global N2O budget is not yet known. Herein, the first observations of N2O concentrations in the Canada Basin (CB) and Greenland Sea Basin (GSB) are presented. A correlation between the historic atmospheric N2O record and N2O concentrations at the corresponding depth in the GSB suggests that the N2O distribution pattern is dominated by air‐sea exchanges and hydrographic processes in this region. The consistency between the observed N2O concentrations in the CB and calculated results based on the above correlation suggest that the N2O concentrations in the CB are most likely dominated by N2O dynamics and subsequent hydrographic processes in the sea adjacent to the GSB. The N2O concentration in the Canada Basin Intermediate Water (CBIW) reflects anthropogenic influences, whereas the N2O concentration in the Canada Basin Deep Water (CBDW) suggests that the CBDW may be a preindustrial "relict."